Ten-Year trends and prevalence of asthma, allergic rhinitis, and atopic dermatitis among the Korean population, 2008-2017 - Jihyun Ha; Seung Won Lee; Dong Keon Yon (The Korean Pediatric Society, 2020)
Background Major questions remain regarding the age-stratified trends of allergic diseases and asthma in Korea. Purpose To identify the estimated recent prevalence and 10-year trends in asthma, allergic rhinitis, and atopic dermatitis among the Korean population from 2008 to 2017. Methods This nationwide cross-sectional survey (Korean National Health and Nutrition Examination Survey) over 10 years (2008-2017) examined representative samples of the Korean population (n=85,006) including 2,131 infants, 4,352 preschool children, 12,919 school-age children, 44,200 adults, and 21,404 elderly adults. Results In the 2016 to 2017 population, the estimated prevalence of asthma was 0.9% in infants, 2.3% in preschool children, 4.1% in school-age children, 2.3% in adults, and 4.1% in the elderly. The estimated prevalence of allergic rhinitis was 9.0%, 20.2%, 27.6%, 17.1%, and 6.9%, respectively. The estimated prevalence of atopic dermatitis was 5.9%, 11.3%, 14.6%, 3.9%, and 1.6%, respectively. Ten-year trends revealed a significant decrease in asthma prevalence in infants, preschool children, and the elderly. and in atopic dermatitis prevalence in infants and preschool children (P<0.05 for all trends). Furthermore, 10-year trends demonstrated a significant increase in allergic rhinitis prevalence in school-age children, adults, and the elderly, and in atopic dermatitis prevalence in school-age children and the elderly (P<0.05 for all trends). Conclusion These results improve our understanding of the age-stratified epidemiology of allergic diseases in Korea and suggest the need for the development of tailored and precise strategies to prevent allergic diseases in different age groups.